Analisis Karakteristik Morfologi dan Pola Pertumbuhan Ikan Uceng Nemacheilus fasciatus (Valenciennes, 1842) pada Sungai Setail, Banyuwangi, Jawa Timur - Kharisma Orchida; Diana Arfiati; Wahyu Endra Kusuma; Syeftyan Muhammad Ali Hamami (Postgraduate, University of Mataram, 2025)
Indonesia's. Setail River is one of the longest rivers in Banyuwangi Regency. Setail River has high potential for fishery biodiversity. One of the fish that is often found in Setail River is Barred loach or known locally as Uceng Fish (Nemacheilus fasciatus). The purpose of this study was to determine the morphological characteristics and determine the relationship between length, weight and condition of Uceng fish in Setail River. Observation of color patterns and special characteristics of sample fish morphologically Nemacheilus fasciatus with characteristics including Having a brown body color, a small elongated body (fusiform). On the body there is a longitudinal black spot pattern, a dorsal pattern resembling a saddle, a homocercal tail fin type, an emarginate tail morphology (slightly concave). The type of mouth is subterminal inferior and has 3 pairs of barbels. Meristic observations of uceng fish have pectoral fins, pelvic fins, dorsal fins, tail fins and anal fins. In this study, an analysis of the relationship between length and weight showed that the growth pattern of the uceng fish was negative allometric and the condition factor obtained the range of condition factor values for male uceng fish during the study at each station for male uceng fish 0.68-1.35 and female uceng fish 0.68-1.40.